The Autotaxin—Lysophosphatidic Acid Axis Promotes Lung Carcinogenesis - Christiana Magkrioti; Nikos Oikonomou; Eleanna Kaffe; Marios-Angelos Mouratis; Nikos Xylourgidis; Iliana Barbayianni; Petros Megadoukas; Vaggelis Harokopos; Christos Valavanis; Jerold Chun; Alexandra Kosma; Georgios T. Stathopoulos; et al. (2018)
Pathogenesis and progression of lung cancer are governed by complex interactions between the environment and host genetic susceptibility, which is further modulated by genetic and epigenetic changes. Autotaxin (ATX, ENPP2) is a secreted glycoprotein that catalyzes the extracellular production of lysophosphatidic acid (LPA), a growth-factor-like phospholipid that is further regulated by phospholipid phosphatases (PLPP). LPA's pleiotropic effects in almost all cell types are mediated through at least six G-protein coupled LPA receptors (LPAR) that exhibit overlapping specificities, widespread distribution, and differential expression profiles. Here we use both preclinical models of lung cancer and clinical samples (from patients and healthy controls) to investigate the expression levels, activity, and biological role of the above components of the ATX/LPA axis in lung cancer. ENPP2 was genetically altered in 8% of patients with lung cancer, whereas increased ATX staining and activity were detected in patient biopsies and sera, respectively. Moreover, PLPP3 expression was consistently downregulated in patients with lung cancer. Comparable observations were made in the two most widely used animal models of lung cancer, the carcinogen urethane-induced and the genetically engineered K-rasG12D -driven models, where genetic deletion of Enpp2 or Lpar1 resulted in disease attenuation, thus confirming a procarcinogenic role of LPA signaling in the lung. Expression profiling data analysis suggested that metabolic rewiring may be implicated in the procarcinogenic effects of the ATX/LPA axis in K-ras- G12D -driven lung cancer pathogenesis.Significance: These findings establish the role of ATX/LPA in lung carcinogenesis, thus expanding the mechanistic links between pulmonary fibrosis and cancer. Cancer Res; 78(13); 3634-44. ©2018 AACR.